Blood lactate during recovery from intense exercise: Impact of inspiratory loading - Chiappa, G. R.; Roseguini, B. T.; Alves, C. N.; Ferlin, E. L.; Neder, J. A.; Ribeiro, J. P. (Medicine & Science in Sports & Exercise, 2008)
Purpose: It has long been suggested that inspiratory muscle activity may impact blood lactate levels ([Lac-]B) during the recovery from dynamic exercise. In this study, we tested the hypothesis that inspiratory muscle activation during recovery from intense exercise would contribute to La- clearance, thus leading to reduced [Lac-]B.